Pendidikan Karakter dan Multikultural Menjawab Pemenuhan Kebutuhan Moral yang Baik di SD Negeri Bandongan 3 Magelang - Lia Nur Rahmawati; Nurhidayah Febiyanti; Khayati Rahayu; Aulia Rizky Amanda; Nisrina Oktaviani; Puji Rahmawati (Prosiding University Research Colloquium, 2022)
This study aims to identify and produce valid information about how the implementation of character and multicultural education in elementary schools. The research method used is a qualitative research method. Information was obtained through observation and interviews with two teachers of the State Elementary School of Bandongan 3 Magelang, which were accompanied by documentation. The data analysis was carried out by method triangulation and data source triangulation. The results of this study indicate that SD Negeri Bandongan 3 Magelang has implemented character and multicultural education well. This is reflected in the school's vision and mission which is supported and realized in the learning process and other activities for students at school.